Visit‐to‐visit heart rate variability is associated with cognitive decline in older adults: The S.AGES cohort: Epidemiology / Risk and protective factors in MCI and dementia. (7th December 2020) - Rouch, Laure; Vidal, Jean‐Sébastien; Hanon, Olivier; ,
Abstract: Background: Visit‐to‐visit blood pressure variability (BPV) has been increasingly recognized as a predictor of cognitive decline and dementia but the impact of long‐term heart rate variability (HRV) on cognition is unknown. Method: 3319 non‐institutionalized subjects from the S.AGES (elderly subjects) cohort underwent clinical examinations every 6 months during 3 years. Visit‐to‐visit HRV was evaluated using standard deviation, coefficient of variation, average real variability, successive variation, variation independent of mean and residual standard deviation. Cognition was assessed using the Mini‐Mental State Examination and incident dementia using the Diagnostic and Statistical Manual of Mental Disorders. Linear mixed models and Cox proportional hazards models were used, respectively to assess the association of HRV with cognitive function over time and incident dementia. Result: Among the 3319 subjects (mean age, 78 years; 57% female; university level, 20%), 93 (2.8%) developed dementia. Higher HRV was significantly associated with poorer cognition (1‐sd increase of CV: β ± SE = ‐0.18 ± 0.06, p < 0.01) after adjustment for demographics, heart rate, antihypertensive drug use, coronary artery disease, diabetes, chronic heart failure, atrial fibrillation, transient ischemic attack or stroke, smoking and dyslipidemia at baseline. Similar results were observed with all other indicators of variability (p<0.01) except residual standard deviation. After adjustment, higher HRV was not associated with greater risk of dementia (1‐sd increase of CV: HR = 1.03, 95% CI [0.83‐1.28], p = 0.7). Conclusion: Higher long‐term HRV is associated with cognitive decline in community‐dwelling older adults. Future research is needed to assess whether it could be a therapeutic target for preserving brain health.